Mesothelin-Targeted CARs: Driving T cells to Solid Tumors - Morello, Aurore (Cancer Discov, 2015)
Chimeric antigen receptors (CARs) are synthetic receptors that target T cells to cell-surface antigens and augment T-cell function and persistence. Mesothelin is a cell-surface antigen implicated in tumor invasion, which is highly expressed in mesothelioma, lung, pancreas, breast, ovarian, and other cancers. Its low-level expression in mesothelia however commands thoughtful therapeutic interventions. Encouragingly, recent clinical trials evaluating active immunization or immune-conjugates in patients with pancreatic adenocarcinoma or mesothelioma have shown responses without toxicity. Altogether, these findings and preclinical CAR therapy models using either systemic or regional T-cell delivery argue favorably for mesothelin CAR therapy in multiple solid tumors.